Isobaric tags for relative and absolute quantitation proteomics analysis of gene regulation by SprC in Staphylococcus aureus. (October 2017) - Zhao, Huanqiang; Hu, Fupin; Yang, Han; Ding, Baixing; Xu, Xiaogang; He, Chunyan; Cui, Zelin; Shu, Wen; Liu, Qingzhong
Aim: To explore the complete gene networks regulated by small RNA SprC and its targets in Staphylococcus aureus .Materials & methods: The isobaric tags for relative and absolute quantitation and bioinformatic methods were utilized to identify and analyze the target proteins affected by SprC in S. aureus N315.Results: Proteomic analysis showed that the expression of 44 proteins was modulated by SprC. Further, bioinformatic analysis displayed that these affected proteins mainly associated with metabolic and cellular process, biological regulation and catalytic activity.Conclusion: Our data provide a rich resource of SprC targets in S. aureus, although the mechanism of regulation by SprC is yet to be elucidated.